PERCEPATAN PERKEMBANGAN KOGNITIF ANAK: ANALISIS TERHADAP KEMUNGKINAN DAN PERSOALANNYA - Ahmad Syarifin (UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: This study was conducted to reveal about efforts to accelerate the development of children. Whether positive implication or otherwise of the child psychologically. Efforts to accelerate the development of children has a negative implication. On the other hand, psychologically it is contrary to the principles and tasks of education itself. The task of educators is not to accelerate cognitive development but to help that child grow proportionately and maximum. Creating a balance so that children can develop an integrative and maximum. Then reinterpretation of the notion that “the sooner the better” to “fast is not necessarily right”.